2020
DOI: 10.3390/genealogy4030069
|View full text |Cite
|
Sign up to set email alerts
|

“They Will Keep Seeing Young Women Murdered by Men. Enough Is Enough-We Have Seen too Many Women Lose Their Lives”. Lessons for Professionals Working with Victims of ‘Honour’ Abuse and Violence

Abstract: The brutal ‘honour’ killing of Banaz Mahmod, aged 20, is still one of the most prominent murder cases of this kind in Britain. This was due partly to its complexity as well as the poor police response to Banaz’s pleas for help before her death—most notably, she reported her abuse on multiple occasions, forewarned them of her murder, and named her killers. This tragic case was a painful example of how professional agencies in the UK fail victims of so called ‘honour’ abuse and violence. Fifteen years on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Minoritised and migrant women face multiple internal and external barriers that prevent them from seeking support ranging from language barriers, lack of knowledge of legal rights and support options, cultural pressures, and fear (Begum, et al, 2020). Mainstream services deny and rationalise domestic abuse against minoritised women which creates a barrier to them being able to access effective support (Femi-Ajao, et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Minoritised and migrant women face multiple internal and external barriers that prevent them from seeking support ranging from language barriers, lack of knowledge of legal rights and support options, cultural pressures, and fear (Begum, et al, 2020). Mainstream services deny and rationalise domestic abuse against minoritised women which creates a barrier to them being able to access effective support (Femi-Ajao, et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Dyer, 2015; Gill, 2008), as well as in vulnerability characteristics, for example, having an insecure immigration status (e.g. Bates, 2021; Begum et al., 2020; Payton, 2014). However, despite recognition of recurring characteristics, limited research exists on the prevalence of each of these characteristics within a larger sample (Bates, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Femi-Ajao et al (2020) found four barriers preventing DVA disclosure to services for Black and minoritised victims in the UK: immigration status, particularly ‘No Recourse to Public Funds’, community influences, lack of interpreters, and unsupportive attitudes from staff within mainstream services. These interconnected barriers are reflected in the under-reporting of DVA for minoritised women (Sundari, 2008; Femi-Ajao et al, 2020) and can prevent victims from seeking support or restrict their ability to leave an abusive environment (Begum et al, 2020; Burman et al, 2004; Dudley, 2017; Sundari 2008). Spousal migrants to the UK are often unaware of their rights and can be manipulated by their perpetrators into believing that they could be deported or separated from their children should they seek support (Begum et al, 2020; DAC, 2021; Harrar, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These interconnected barriers are reflected in the under-reporting of DVA for minoritised women (Sundari, 2008; Femi-Ajao et al, 2020) and can prevent victims from seeking support or restrict their ability to leave an abusive environment (Begum et al, 2020; Burman et al, 2004; Dudley, 2017; Sundari 2008). Spousal migrants to the UK are often unaware of their rights and can be manipulated by their perpetrators into believing that they could be deported or separated from their children should they seek support (Begum et al, 2020; DAC, 2021; Harrar, 2021). However, deportation is a possible outcome and insecure status engenders fear of services (Chantler et al 2003; Dudley, 2017; Sundari, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation